Bazı Bitki Geli im Düzenleyicilerin Pinus silvestris L. Fidecik Morfolojik Karakterlerine Etkisi - Sıvacıoğlu, Ahmet; Ayan, Sezgin; Gülerol, Bilal (Kastamonu Üniversitesi Orman Fakültesi Dergisi;Cilt:7 No: 2, 2007)
In this study, the Bolu-Alada originated scots pine seeds were sowed onto the seedbeds of Bolu Forest Nursery after soaking for 24 hours into the 200-400-600 ppm concentration of GA3, 50-150-300 ppm concentration of IBA+NAA and 20-50-100 ppm concentration of Kinetin for determining the effects of plant growth regulators (phytohormones) on the morphological characters of Scots pine (Pinus silvestris L.) seedlings. After 36 days when the primary leaves emerged, the seedlings were lifted and some parameters as root collar diameter (RCD), root length (RL), hypocotyls length (HL), epicotyls length (EL), cotyledon number (CN), cotyledon length (CL), root fresh weight (RFW), stem fresh weight (SFW), root dry weight (RDW), stem dry weight (SDW) were measured on them. By investigating morphologic characters of the seedlings, determination of the advantage of plant growth regulators on seedling growth and production was aimed. There are no statistical differences on RCD, CL, CN, SDW characters after the treatments. The biggest values of RCD (0,87 mm), CN (6.55 unit), CL (2.23 cm), SDW (6,36 mg) were obtained for IBA+NAA. Despite of the fact that there is no effect of hormone x dose interaction on RL, the biggest RL (7,95 cm) was obtained for 600 ppm GA3. Hormone and hormone x dose interaction affect the EL and HL. The biggest HL and EL values (HL = 1.30 cm, EL = 0.34 cm) were determined for GA3, as to the dose for 400 ppm GA3 (HL = 1.417 cm, EL = 0.37 cm). The hormone kind affects the RFW, SFW and RDW and the biggest values were obtained as 22,33 mg, 36,63 mg, and 3,82 mg for IBA+NAA, respectively.
The Effects of the Some Plant Growth Regulators on Morphological Traits of Scots Pine Seedlings
Keywords: Plant growth regulators, Phytohormone, Scots pine, Seedling